2017
DOI: 10.1200/jop.2016.015859
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients and Oncologists Discuss the Cost of Cancer Treatment? An Observational Study of Clinical Interactions Between African American Patients and Their Oncologists

Abstract: Purpose: Financial toxicity negatively affects patients with cancer, especially racial/ethnic minorities. Patient-oncologist discussions about treatment-related costs may reduce financial toxicity by factoring costs into treatment decisions. This study investigated the frequency and nature of cost discussions during clinical interactions between African American patients and oncologists and examined whether cost discussions were affected by patient sociodemographic characteristics and social support, a known b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 54 publications
1
46
0
Order By: Relevance
“…Improving patients' knowledge of treatment costs may also represent a promising strategy to improve financial outcomes. Although most patients with cancer want to discuss treatment costs with their physicians (43,44), research suggests that cost discussions happen infrequently when patients and oncologists discuss treatment options, and may focus more on indirect costs such as missing work than on direct costs such as out-of-pocket costs and copayments (45). Improved cost discussions between patients with cancer and their oncologists could help patients make more informed treatment decisions (19,(46)(47)(48), connect patients with financial support (49), and potentially reduce financial hardship related to cancer (19,46,47,50).…”
Section: Discussionmentioning
confidence: 99%
“…Improving patients' knowledge of treatment costs may also represent a promising strategy to improve financial outcomes. Although most patients with cancer want to discuss treatment costs with their physicians (43,44), research suggests that cost discussions happen infrequently when patients and oncologists discuss treatment options, and may focus more on indirect costs such as missing work than on direct costs such as out-of-pocket costs and copayments (45). Improved cost discussions between patients with cancer and their oncologists could help patients make more informed treatment decisions (19,(46)(47)(48), connect patients with financial support (49), and potentially reduce financial hardship related to cancer (19,46,47,50).…”
Section: Discussionmentioning
confidence: 99%
“…The digital divide (i.e., computer literacy and internet access) still exist by race and socioeconomic position, and access to the internet is still less stable for racial/ethnic minorities as well as rural populations (129). Additionally, those who are financially stable may experience periods of economic insecurity attributable to their health status (130, 131); these occurrences may not allow them to participate fully and interventions that rely on web-based technologies like Wi-Fi connections. Thus, researchers that rely on smartphones and their related apps may be able to overcome some of these technological disparities, but may encounter other phone-related challenges (i.e., data, screen size, vision, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Cost discussions allow patients to select lower-priced alternatives when available, make a trade-off between medical benefit and cost based on their preference, and identify financial assistance resources earlier rather than later [21]. A recently published qualitative study offered important insights on topics that were covered during cost communication [22]. The study found that only\10% of the discussions were related to out-ofpocket costs, with time off work and insurance being the two dominating topics in cost-related discussions.…”
mentioning
confidence: 99%